Objects of expansion of Byzantina Empire to the East (10th - 11th centuries). Terminology - Viada Arutyunova-Fidanyan (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article deals with the development of main terms referring to spatial and administrative objects of expansion of the Byzantine Empire to the East. In the “Caucasian Dossier” by Constantine Porphyrogennetos most often occur the terms chora and chorion. In everyday speech these terms were synonymous but the authors of the “Caucasian Dossier” diff erentiate them (at least, with regard to the size). An analysis of verbal elements in this material is made more diffi cult by the fact that the Armenian-Chalcedonite nobility habitually used the phrase ašxarh hayoċ to refer to land possessions of Armenian rulers that came to be in the sphere of infl uence of the Empire, and in their reports to the Byzantine court used the lexeme chora as an equivalent to ašxarh. The “land” of the Taronites, the “land” of the Iberian Bagratids is a common possession of noble families, and the eff orts of Byzantine emperors to get a hold on lands of a certain aristocrat usually faced active resistance of his family. Agreements of this period with the Taronites and the Iberian Bagratids demonstrate initial stages in the process of transition from allies’ relationship to that of vassals.